Press of the Polish bibliophilic movement in library resources and their importance for book studies - Andrysiak, Ewa (Interdyscyplinarium nauk o mediach i kulturze, 2020)
In the article the author mentions journals of Polish bibliophiles: from the oldest going back to the early 1900’s, through the interwar period, when the organized bibliophilia movement was taking place. Simultanously with the movement, journals concerning bibliophilia and bookplates occurred, which constitute an important part of the publishings of the movement. In addition to the well-known journals dating from the interwar period, the author discusses journals published by Polish bibliophilia associations after the World War II. She also refers to the importance of the bibliophilia journals, and, in a more general meaning, to the bibliophilia movement in Polish bibliology.